2021
DOI: 10.1007/s00296-021-04980-7
|View full text |Cite
|
Sign up to set email alerts
|

Differences and similarities of multisystem inflammatory syndrome in children, Kawasaki disease and macrophage activating syndrome due to systemic juvenile idiopathic arthritis: a comparative study

Abstract: To compare the clinical and laboratory findings of multisystem inflammatory syndrome in children (MIS-C), patients with Kawasaki disease (KD) and with macrophage activating syndrome due to systemic juvenile idiopathic arthritis (sJIA-MAS) on real-life data. Patients diagnosed with MIS-C, KD, and sJIA-MAS from 12 different centers in Turkey who were followed for at least 6 months were included in the study. Demographic, clinical, and laboratory findings of all patients were analyzed. A total of 154 MIS-C, 59 KD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 38 publications
8
56
0
Order By: Relevance
“…Diversity between the two illnesses is also obvious as there are signs and symptoms with high frequency in MIS-C which are less commonly or rarely presented in KD patients. For example, gastrointestinal symptoms are more common for MIS-C according to many studies including our observation ( 11 , 22 , 29 ). It should also be noted that among the studied patients with gastrointestinal disorders in our MIS-C group, one had acute appendicitis, which required laparoscopic appendectomy, and the “white” appendix was removed.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Diversity between the two illnesses is also obvious as there are signs and symptoms with high frequency in MIS-C which are less commonly or rarely presented in KD patients. For example, gastrointestinal symptoms are more common for MIS-C according to many studies including our observation ( 11 , 22 , 29 ). It should also be noted that among the studied patients with gastrointestinal disorders in our MIS-C group, one had acute appendicitis, which required laparoscopic appendectomy, and the “white” appendix was removed.…”
Section: Discussionsupporting
confidence: 59%
“…HScore >105 was associated with the severest signs of MIS-C: myocarditis [OR = 4.2 (95% CI: 1.5, HScore is a simple tool which might be used for assessment of severity of MIS-C. Additionally, there is a difference in platelet levels in MIS-C and KD patients in our study, with median of 185 and 520 * 10 9 /l, respectively. Thrombocytosis is typical for KD, but less common in MIS-C patients, who quite often have a tendency toward thrombocytopenia, especially at onset or during the peak of the disease (8,20,22,29). Additionally, elevated biochemical markers of cardiac injury and highly elevated ferritin and D-dimer are typical for MIS-C patients (20,22,29).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence supporting this theory incorporates the resemblance of MIS-C and Kawasaki disease, a known vasculitis ( 35 37 ). Similar features of these two inflammatory disorders include prolonged fever, increased inflammatory markers, rash, non-exudative conjunctivitis, and mucous involvement (cracked lips, strawberry tongue) ( 33 , 35 37 ). Despite these resemblances, there are also marked differences in clinical manifestations, such as older age of onset, more frequently observed gastrointestinal involvement, and a more severe disease course in MIS-C, as well as dissimilarities in laboratory findings, such as lymphopenia, thrombocytopenia, and elevated D-dimer levels in MIS-C ( 33 , 35 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar features of these two inflammatory disorders include prolonged fever, increased inflammatory markers, rash, non-exudative conjunctivitis, and mucous involvement (cracked lips, strawberry tongue) ( 33 , 35 37 ). Despite these resemblances, there are also marked differences in clinical manifestations, such as older age of onset, more frequently observed gastrointestinal involvement, and a more severe disease course in MIS-C, as well as dissimilarities in laboratory findings, such as lymphopenia, thrombocytopenia, and elevated D-dimer levels in MIS-C ( 33 , 35 , 37 ). Comparison of inflammatory cells and 180 plasma proteins in patients with MIS-C and Kawasaki disease revealed that both conditions have elements of hyperinflammation and vasculitis but a different cytokine pattern, suggesting different pathogenesis ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation